Central Pathways Integrating Metabolism and Reproduction in Teleosts - Shahjahan, Md; Kitahashi, Takashi; Parhar, Ishwar S. (Frontiers in Endocrinology, 2014)
Energy balance plays an important role in the control of reproduction. However, the cellular and molecular mechanisms connecting the two systems are not well understood especially in teleosts. The hypothalamus plays a crucial role in the regulation of both energy balance and reproduction, and contains a number of neuropeptides, including gonadotropin-releasing hormone (GnRH), orexin, neuropeptide-Y (NPY), ghrelin, pituitary adenylate cyclase-activating polypeptide (PACAP), α-melanocyte stimulating hormone (α-MSH), melanin-concentrating hormone (MCH), cholecystokinin (CCK), 26RFa, nesfatin, kisspeptin, and gonadotropin-inhibitory hormone (GnIH). These neuropeptides are involved in the control of energy balance and reproduction either directly or indirectly. On the other hand, synthesis and release of these hypothalamic neuropeptides are regulated by metabolic signals from the gut and the adipose tissue. Furthermore, neurons producing these neuropeptides interact with each other, providing neuronal basis of the link between energy balance and reproduction. This review summarizes the advances made in our understanding of the physiological roles of the hypothalamic neuropeptides in energy balance and reproduction in teleosts, and discusses how they interact with GnRH, kisspeptin, and pituitary gonadotropins to control reproduction in teleosts.